An Address to Jews and Other People of Conscience - Knopf, Michael R. (Interpretation, 2025)
Antisemitism is on the rise in the U.S. and around the world. Hatred of Jews is part of a trend of hatred against many minoritized groups—hate speech and violence against one group signals a rise in hatred toward other targeted groups. This essay promotes the Jewish teaching that all of us are responsible for bringing good into the world as we actively and relentlessly counter evil. The essay explores the rich heritage of ancient and modern Jewish teachings and traditions as a source of wisdom for how all people can work together to redeem our world.